Distribution of stream macroalgal communities from the mid-western region of Paraná state, southern Brazil: importance of local scale variation - Branco,Ciro Cesar Zanini (2009)
Twenty-two stream segments, representing the diverse types of environments in the mid-western region of the Paraná State, southern Brazil, were sampled for occurrence of macroalgal communities from May to October in 2002. Twenty-seven macroalgal taxa were found, with Chlorophyta as the dominant algal group, followed by Cyanobacteria, Rhodophyta and Chrysophyta. The most widespread species was Phormidium retzii. Distribution was patchy, with species number per sampling sites ranging from zero to six and correlated positively with the abundance. On the other hand, no significant correlation was found among the species number and abundance with environmental variables. Results indicated wide and random variation among the streams. Thus, it seemed that the distribution of macroalgal communities in the study area responded more closely to the local-scale variation than the regional characteristics.